Nutritional and reproductive status affect amino acid appetite in house crickets (Acheta domesticus) - Tierney, Ann Jane; Velazquez, Elizabeth; Johnson, Lauryn; Hiranandani, Sarah; Pauly, Meghan; Souvignier, Maya (Frontiers in Insect Science, 2023)
We examined amino acid appetite in the omnivorous house cricket (Acheta domesticus), a common model organism for both research and teaching. Our first experiment addressed the hypothesis that house crickets can discriminate between sucrose and essential amino acids (EAA), and that preference for the latter would be affected by prior feeding experience. To test this hypothesis, we compared feeding responses of juvenile and adult crickets following pre-feeding with sucrose or an essential amino acid mixture, predicting that sucrose-only pre-feeding would enhance subsequent intake of amino acids in a two-choice preference test. Based on previous studies, we also predicted that amino acid consumption would be enhanced in females compared to males, and in mated compared to virgin females. Hence we compared responses in male and female last instar nymphs, adult males, virgin females, mated females, and mated females allowed to lay eggs. The second experiment examined how extended periods of essential amino acid deprivation (48 h to 6 days) affected appetite for these nutrients in adult male and female insects. Finally, we examined growth and survival of juvenile and adult crickets fed a holidic diet lacking all amino acids and protein. Our results demonstrated that house crickets can distinguish EAA from sucrose and that consumption of the latter is enhanced following sucrose-only pre-feeding. We also found sex and developmental differences, with juvenile and virgin females showing a greater preference for EAA than juvenile or adult males. Contrary to expectation, mated females preferred sucrose over EAA both prior to and after egg laying. We also found that the crickets of both sexes increased their intake of EAA when exposed to longer periods of deprivation, indicating that they engage in compensatory feeding on these nutrients. Finally, as expected we found that growth was severely limited in juveniles fed a diet lacking all amino acids, but adults and many juveniles survived for 30 days on this diet.